Aplicação de ferramentas lean para impulsionar melhorias no tempo de setup em empresas do setor de cuidados pessoais - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The study deals with the application of Lean tools to drive improvements in setup time in companies in the personal care sector. With the aim of reducing setup times between sessions of aesthetic procedures for personal care. The specific objectives are analyse the flow of patient care according to the sequence of appointments, evaluation of room organization standards, evaluation of patient care procedures, evaluation of patients personal care protocols, estimation of average housekeeping time booths to receive patients with appointments and tools to map the process and reduce setup time to start scheduled sessions. As a methodology a bibliographical survey, mapping of processes, survey of preparation and service times, evaluation of performance indicators, action plan, implementation of actions and monitoring of possible results were carried out. The observation detects that the application of Lean tools can help to improve the company's setup time, since it is commonplace to identify the improvement of times and the standardization of deadlines for the execution of service protocols. In this way, this work suggests that the application of Lean tools can help the personal care company to reduce the delays to start the scheduled sessions of the aesthetic procedures, since there was an average reduction of 26% in the waiting time between patient care and reduction 25% in the number of stages performed per service.
Keywords: Produção enxuta; ENGENHARIAS: ENGENHARIA DE PRODUCAO; Lean; Setup; VSM; SMED; Estética